Formation of Ian McEwan’s artistic perspectivism - Maksim A. Rozanov (Семиотические исследования)
Artistic perspectivism is considered to be the author’s value-based creative will. From this perspective, we analyse the formation of Ian McEwan’s specific perspectivism based on his first novels The Cement Garden and The Comfort of Strangers. In addition, the connection between the writer’s value orientation embodied in the above-mentioned works and his non-creative consciousness is considered. This connection explains the significance of the category of the boundary for I. McEwan’s artistic perspectivism. In the writer’s debut novel, his anti-Rousseau positions are revealed – I. McEwan considers the absence of externally imposed restrictions as a situation in which a person’s relationship with the Other is traumatized, and boundaries in the inner world of the individual are built under the influence of the natural principle that has prevailed over it. Further, the development of the writer’s creative perspectivism in the early 1980s is explored. Based on his understanding of the relationship between a person’s inner world and externally established boundaries as the most significant communication in the context of personality formation, I. McEwan raises the question of how much interpersonal relationships are conditioned by desires, fears, and behavioral patterns formed in childhood. The study reveals the vector of development of I. McEwan’s artistic perspectivism formed in the 1980s. It is concluded that the ethical view of the writer on conflicts related to the internal boundaries of the individual, which was formed in his early works, determined the value orientation of his novels until the 2010s.